THE CORAL REEF CONDITION IN TURELOTO BEACH NORTH NIAS REGENCY NORTH SUMATERA PROVINCE - Romeo '; Thamrin '; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research of coral reef was conducted in May in Tureloto Beach of North Nias, North Sumatera Province. The research was aimed to analyze the condition of coral reef and to observe coral reef base on diversity index, uniformity index and dominance index. The study used survey method by applying Line Intercept Trasect (LIT) which consisting of three main stations. Each station was divided into two sub depths, i, e. 3 and 10 m respectively.The type of coral reef in Tureloto Beach was fringging reef. Coral lifeform’s found in the area were Acropora Branching (ACB), Acropora Encrusting (ACE), Acropora Submassive (ACS), Acropora Digitate (ACD), Acropora Tabulate (ACT), Coral Branching (CB), Coral Massive (CM), Coral Encrusting (CME), Coral Submassive (CS), Coral Foliose (CF), Coral Meliopora (CME), Coral Heliopora (CHL) and Coral Mushroom (CMR). The conditions of coral reef at the depth of 3 m was bad with percentage of 19,23%, percentage conditions of coral reef at the depth 10 m is 54,06% with category its good.Keywords : Tureloto Beach, Coral Reef, Acropore